Soil Fertility Status of Organic Paddy Experiment - Mujiyo Mujiyo; Bambang Hendro Sunarminto; Eko Hanudin; Jaka Widada (Faculty of Agriculture, Universitas Sebelas Maret, 2015)
The study aims to determine fertility status of the soil after organic paddy experiments using kinds and doses of organic fertilizers. Experiment was conducted at greenhouse laboratory in Faculty of Agriculture Sebelas Maret University Surakarta. Experimental design used completely randomized design with 9 kinds of treatment was replicated 3 times. Experiments were the use of cow manure, Azolla fertilizer, Azolla inoculum and its combinations that are based on fulfilling nutrient requirements of 120 kg N ha-1.Result shows that the use of cow manure, Azolla fertilizers and Azolla inoculum had no effect on changes of soil fertility status. Soil fertility status was not significantly correlated with cow manure (0,16ns), Azolla fertilizer (0,26ns) and Azolla inoculum (0,16ns). Average of final soil fertility status included fertile category, which was similar as the initial soil fertility status. Average of final soil properties of treatment but nevertheless was relatively higher than in no treatment, indicating the use of cow manure, Azolla fertilizer, Azolla inoculum and its combinations had greater impact to soil properties. Cow manure despite increased available K2O and dry grain, but it did not significantly increase the soil fertility status from fertile to very fertile. This was presumably due to the relatively short experiment period, only one planting season had not given significant effect to soil properties. Implication of this study is the use of cow manure, Azolla fertilizer, Azolla inoculum and its combinations although did not increase the soil fertility status but could maintain soil fertility status as the initial conditions before planting.